Inhibition of Photosynthetic Electron Transport by Diphenyl Ether Herbicides - Bugg, M. Wayne (1980)
The effects of the diphenyl ether herbicides HOE 29152 (methyl-2[4-(4-trifluoromethoxy) phenoxy] propanoate) and nitrofluorfen (2-chloro-1-[4-nitrophenoxy]-4-[trifluoromethyl]benzene) on photosynthetic electron transport have been examined with pea seedling and spinach chloroplasts. Linear electron transport (water to ferricyanide or methylviologen) is inhibited in treated chloroplasts, but neither photosystem II activity (water to dimethylquinone plus dibromothymoquinone) nor photosystem I activity (diaminodurene to methylviologen) is affected. Cyclic electron flow, cata-lyzed by either phenazine methosulfate or diaminodurene, is resistant to inhibition by nitrofluorfen. In diphenyl ether-treated chloroplasts the half-time for the dark reduction of cytochrome f is increased 5- to 15-fold. These data indicate that the site of inhibition for the diphenyl ethers is between the two photosystems in the plastoquinone-cytochrome f region.